O lugar da fotografia na cena teatral paulistana no século XXI - Sousa, Bob [UNESP] (2015)
By intermediate of the project I performed an investigation about the role of photography and the photographer's vision, inserting myself, in different ways, on the theater presentations of São Paulo's city groups, in distinct spaces: the black box, the street and the hybrid spaces. Thereby, in order to lead the established cut to term, I pursuited gather pressuposed historical and esthetic concerning the image studies and social practice, group practice (in its phenomenal determinant nature: the spectacle), introducing visual documents (photographic support) as potent instrument in the verifiable way of an exterior perspective to their producers. Photography in the passive index of analysis and contrast the desired and the reachable. From the epistemological point of view, the reflection offers the comparison and articulation of the concerning aspects to a certain theory of visuality, identity, memory, territorial locus